Utilizing Rice (Oryza sativa) Hulls as a Sustainable Alternative to Sand in Cookstove (Dalikan) Manufacturing: Social and Environmental Benefits - Ruby May V. Barcena; Princess Anne S. Galera; John Patrick B. Laureta; Johnler Q. Magalim; Kent Jason N. Sumalag (Al Mabhats : Jurnal Penelitian Sosial Agama, 2025)
This study evaluates the acceptability of rice husk (Oryza sativa) as an alternative material to sand in household cookstove production, focusing on usability, durability, and appearance. Employing a descriptive-experimental design, the research involved thirty selected households in Peñarrubia, Abra, distributing respondents evenly across three barangays. Data were collected using an adapted assessment sheet and analyzed through weighted mean and ANOVA at a 0.01 significance level. Results showed Treatment 1 had moderate acceptance (mean=3.22), Treatment 2 achieved high acceptance (mean=3.57), and Treatment 3 comprising 5 kg cement and 5.7 kg rice husk attained the highest acceptance (mean=4.73), indicating very high user approval. Statistical analysis confirmed significant differences among treatments. These findings highlight rice husk’s potential as an effective and socially acceptable sand substitute in cookstove manufacturing. Additionally, they underscore its role in promoting environmental responsibility and sustainable resource utilization, contributing to community well-being by offering a practical, eco-friendly cooking technology. This aligns with broader social goals of waste valorization and local economic empowerment through innovation.